2014
DOI: 10.12659/msm.891361
|View full text |Cite
|
Sign up to set email alerts
|

Postural Sway and Motor Control in Trans-Tibial Amputees as Assessed by Electroencephalography during Eight Balance Training Tasks

Abstract: BackgroundThe purpose of this study was to investigate the changes in the Power Spectral Density (PSD) of the electroencephalogram (EEG) during 8 common sensorimotor balance training tasks of varying difficulty in single-limb trans-tibial amputees.Material/MethodsEight sensorimotor balance exercises, including alteration in vision, base of support, and surface compliance, were used to test postural control and how it related to the electroencephalogram (EEG). A control group was compared to a group of people w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 47 publications
0
15
1
2
Order By: Relevance
“…Beta band power increased in the virtual-reality condition in the frontal and occipital regions for both groups. Petrofsky and Khowailed (2014) also observed an increase in beta power as balance challenges increased in central and parietal areas of both controls and amputee patients. Tse et al (2013) also found increase in beta power with increase in balance challenge task (base of support or surface compliance) in the parietal and central areas.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…Beta band power increased in the virtual-reality condition in the frontal and occipital regions for both groups. Petrofsky and Khowailed (2014) also observed an increase in beta power as balance challenges increased in central and parietal areas of both controls and amputee patients. Tse et al (2013) also found increase in beta power with increase in balance challenge task (base of support or surface compliance) in the parietal and central areas.…”
Section: Resultsmentioning
confidence: 89%
“…In contrast, Pirini et al (2011) observed a decrease in alpha power during eyes-open task in the right inferior parietal area, which is in line with the increased attention required to perform a balance under degraded conditions. Petrofsky and Khowailed (2014) also observed an increase in activation with increased balance challenge, finding an overall signal power increased with a decrease in the amount of qality of sensory feedback. Likewise, Tse et al (2013) observed an increase in beta and sigma bands in parietal and central areas with a more difficult balance challenge.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations